Subcellular localization of HMGB1 in human cholangiocarcinoma: correlation with tumor stage - Nattawan Suwannakul (Springer, 2021)
Abstract Cholangiocarcinoma (CCA) is a malignant disease with a poor prognosis, and several studies have been conducted using different molecular markers as a tool for CCA diagnosis, including Clonorchis sinensis (CS)-CCA. We initially identified the expression profiles of the three markers of interest, HMGB1, SOX9, and YAP1, using GSE (GSE76297 and GSE32958) datasets. Upregulated levels of these three proteins were detected in CCA samples compared to those in normal samples. To clarify this issue, 24 human CCA tissues with paired adjacent normal tissues were evaluated using immunohistochemical staining. Of the three markers, the total cellular staining intensities were scanned, and subcellular localization was scored in the nuclear and cytoplasmic regions. The intensities of HMGB1, SOX9, and YAP1 were elevated in CCA tissues than the adjacent normal tissues. Individual scoring of subcellular localization revealed that the expression levels of HMGB1 (nucleus) and YAP1 (nucleus and cytoplasm) were significantly different from the pathologic M stage. Moreover, the translocation pattern was categorized using “site-index”, and the results demonstrated that the overexpression of HMGB1 and SOX9 was mostly observed in both the nucleus and cytoplasm, whereas YAP1 was predominantly expressed in the cytoplasm of tumor cells. Interestingly, the site index of HMGB1 was moderately correlated with the tumor stage (r = 0.441, p = 0.031). These findings imply that the overexpression of subcellular HMGB1 could be associated with the metastatic status of patients with CS-CCA, which was shown to be effective for CS-CCA prognosis.